The In Vitro study on the effect of selected commercially available mouthrinses on singleand mixed–species bacterial biofilms / Tayyaba Fatima - Tayyaba, Fatima (2017)
Oral cavity, like other locales of human body harbors the micro-florae which are distinctively distributed in various sites and surfaces of the mouth. The normal ecology of the oral cavity should be maintained and hence, the use of oral rinse with antibacterial agent should be used without completely killing the bacteria or compromising the normal oral ecology. Commercially available oral rinses contain active ingredient(s) with concentration that is claimed by manufacturers to be effective as antiplaque agent. To date there has been no mention of the effect of oral rinse on the adherence of early plaque colonizers in plaque formation. There is also no mention of suitable time to use the oral rinse (before or after meals). The aim of the study was to determine i) the bacterial adherence to the experimental pellicle pretreated with oral rinse and ii) the bacterial retention in the biofilm treated with oral rinse compared with their negative controls. An artificial mouth (NAM) system was used for the development of single-species biofilm (Actinomyces viscosus, Streptococcus mitis, and Streptococcus sanguinis respectively) and dual-species biofilm (A. viscosus + S. mitis and A. viscosus + S. sanguinis respectively). Three commercially available oral rinses containing active ingredients [Essential oils (EO), Chlorhexidine gluconate (CHX) and Cetylpyridinium chloride (CPC)] were used. The effect of the oral rinse was assessed using two concentrations (100% and 50%) for CPC and CHX and one concentration (100%) for EO. For the adherence study the experimental pellicle on the beads (in the capillary tubes of the NAM system) was pretreated with the oral rinse before the inoculation of bacteria, this would resemble the use of rinse before meal. In the retention study, the biofilm was formed first before treating with the oral rinse and this corresponds to the use of oral rinse after meal. The bacterial population of the biofilm was determined using serial dilution assay and expressed as colony forming unit per ml. Deionized distilled water was used in place of oral rinse and served as a negative iv control. For the qualitative study of bacterial population viewing was carried out using Scanning Electron Microscope (SEM). It was observed that on treatment with the oral rinses (100%) the bacterial population of S. mitis, S. sanguinis and A. viscosus of both studies (adherence and retention) was significantly reduced where the reduction was less for EO-based oral rinse compared with that of CHX and CPC in the following sequence EO<CHX<CPC) (p<0.05). Moreover it was observed that bacterial population in the respective biofilms where the experimental pellicle was pretreated with the oral rinse before bacterial inoculation (bacterial adherence) was higher compared with that where the oral rinse was used after the bacterial inoculation (bacterial retention). From the results, it appears that oral rinses at their commercially available concentration (100% of the original concentration) with respect to those containing CPC and CHX to be preferably used before meal and EO after meal. A 50% of the original commercial concentration of oral rinses containing CPC and CHX can be recommended for use after meals.